2022
DOI: 10.1538/expanim.21-0120
|View full text |Cite
|
Sign up to set email alerts
|

Morris water maze: a versatile and pertinent tool for assessing spatial learning and memory

Abstract: Since its development about 40 years ago (1981–2021), Morris water maze has turned into a very popular tool for assessing spatial learning and memory. Its many advantages have ensured its pertinence to date. These include its effectiveness in evaluating hippocampal-dependent learning and memory, exemption from motivational differences across diverse experimental manipulations, reliability in various cross-species studies, and adaptability to many experimental conditions with various test protocols. Nonetheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 202 publications
0
50
0
Order By: Relevance
“…P < 0.001) in animal models of AD. However, when using a large pool diameter or shrinking the platform-site size, platform crossings measured during the trials may be biased (Othman et al, 2022 ). The pool diameters of the included studies used were 100 cm (Liu et al, 2022 ), 120 cm (Cho et al, 2015 ; Li et al, 2022 ; Xu et al, 2022 ) and 150 cm (Zhao et al, 2020 ) and platform diameters were 9 cm (Xu et al, 2022 ), 10 cm (Li et al, 2022 ) and 12 cm (Zhao et al, 2020 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…P < 0.001) in animal models of AD. However, when using a large pool diameter or shrinking the platform-site size, platform crossings measured during the trials may be biased (Othman et al, 2022 ). The pool diameters of the included studies used were 100 cm (Liu et al, 2022 ), 120 cm (Cho et al, 2015 ; Li et al, 2022 ; Xu et al, 2022 ) and 150 cm (Zhao et al, 2020 ) and platform diameters were 9 cm (Xu et al, 2022 ), 10 cm (Li et al, 2022 ) and 12 cm (Zhao et al, 2020 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Morris water maze is a frequently used behavioral test to assess hippocampal-centered spatial reference and working memory. 68 It has been documented that lesions in the dorsal hippocampus and striatum, 69 along with the cerebral cortex, basal forebrain and cerebellum impair Morris’s water maze performance. 70 Concerning this, it is notable that chronic ethanol consumption causes lesions in the hippocampus and cerebral cortex possibly by increasing both AChE activity and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…For the probe trial, the most frequent parameter used is time spent in the target quadrant compared to the other quadrants [ 57 ]. A longer time spent in the target quadrant reflects a superior retrieval memory [ 58 ]. In the present study, we found that T2DM VaD rats displayed an increased escape latency time compared to normal rats, indicating reduced spatial learning and memory throughout the task.…”
Section: Discussionmentioning
confidence: 99%